Interpretation of Railway On-Train Data of Electrical Train Service (ETS) in Malaysia - MOHAMED NAZUL, MUHAMMAD AZKI HAFIZI; NGALI, MOHD ZAMANI; MD JALIL, MOHD AZLIS SANI (Research Progress in Mechanical and Manufacturing Engineering, 2022)
On train data recorder (OTDR) widely use in rail transportation. Industry 4.0 is currently trend on extensive use of data. Railway transportation is complex Railway systems are technologically complex, including diverse human actors, organizations, and technology solutions. The utilization of OTDR currently has been used for the purpose of monitoring system. Form existing on board data this study discovers new method interpreting data for other purpose. The objective of this study is to interpret raw mechanical data from Keretapi Tanah Melayu Berhad (KTMB). This study focusses on pre-existing data with introducing different tools of interpreting from previous research. The method was used based on research methodology and finding on literature review to achieve research objective. A few recommendations were suggested to use future study with using OTDR as the main source of data.